ChemInform Abstract: Silver Triflate Catalyzed Cyclopropyl Carbinol Rearrangement for Benzo[b]oxepine and 2H‐Chromene Synthesis. Issue 46 (November 2015) - Chan, Philip Wai Hong; Teo, Wan Teng; Koh, Shaun Wei Yong; Lee, Bo Ra; Ayers, Benjamin James; Ma, Dik‐Lung; Leung, Chung‐Hang
Abstract A wide range of functionalized oxygen heterocycles are obtained by a general method starting from 2‐[cyclopropyl(hydroxy)methyl]phenols.